Способи підвищення коефіцієнта корисного використання маси акумулюючого матеріалу в акумуляторах теплоти фазового переходу] - Горобець, В. Г.; Антипов, Є. О.; Троханяк, В. І.; Богдан, Ю. О. (Енергетика і автоматика, 2017)
UDC536.248.2Ways to improve efficiency USE WEIGHT accumulating material in theHEAT ACCUMULATOR OFPHASETRANSITIONV.Gorobets, I. Antypov, V. Trohanyak, Y. Bogdan Experimental studies the efficiency of accumulating material (AM) phase transition in terms of thermal power found shortcomings in its design. In particular, since the phase transition is not the entire thickness of the material at the same time, that spread heat flow in the volume of the material is uneven, there is a need to improve the design of heat transfer surface such accumulators. However, to improve efficiency using mass accumulating material, all proposed technical solutions should be directed to ensure optimal redistribution of temperature fields throughout the volume of the AM.The purpose of research–increase efficiency using mass accumulating material in the heat accumulator of phase transition.Materials and methods of research. As a result of experimental studies  and numerical modeling revealed the presence of areas of low rate of melting accumulating material which is in the lower range of heat sources. The difference between the values of the temperature in the initial and final stage of melting in quantities upper and lower levels do not exceed ± 5 ÷ 7 ° C. The above indicates the low efficiency of the mass of material accumulating lower levels and demonstrates the need for redistribution of temperature fields in the bulk of the material.Therefore, in order to improve efficiency using mass accumulating material lower levels proposed advanced heat accumulator of phase transition design, which compared with the previous model, has some design changes in a wave-like bottom.Results of research. For comparative analysis and study of advanced heat accumulator designs use heat phase transition coefficient weight of useful accumulating material which is determined by the provisions of [5–7]. Conducted exergic analysis shows that in terms of useful weight as in the first and second embodiments, the number of accumulating material that was effectively involved under equal conditions of work, the same. But in the second version, it works efficiently M2> M1 by changing the geometry of the design in the bottom of the heat accumulator of phase transition casing.Analysis of the data shows that performance wavy forms the bottom of the cabinet, provided a growth factor useful mass accumulating material 36% for the same heat output of the sample-analogue.However, the melting profiles AM in the heat accumulator of phase transition and improved study designs are similar, but there is a maximum temperature at the bottom of the wall and the bottom casing of the heat respectively 15 % and 7 % more than the same amount of heat accumulatorAM study design. Conclusions• To reduce the amount of «dead zones» in accumulating material to minimize its bottom hull perform an undulating shape.2. The comparative analysis of the energy accumulators of heat in the «category» showed that the mass ratio useful heat accumulating material improved heat accumulator design is 36 % higher compared to the study.3. It is established that the temperature of the material at the bottom and the bottom of the housing wall heat accumulator improved design for 7 % and 15 % higher than in the bulk material accumulating unit study design.